2017
DOI: 10.1111/ele.12874
|View full text |Cite
|
Sign up to set email alerts
|

Bottom‐up vs. top‐down effects on terrestrial insect herbivores: a meta‐analysis

Abstract: Primary consumers are under strong selection from resource ('bottom-up') and consumer ('topdown') controls, but the relative importance of these selective forces is unknown. We performed a meta-analysis to compare the strength of top-down and bottom-up forces on consumer fitness, considering multiple predictors that can modulate these effects: diet breadth, feeding guild, habitat/environment, type of bottom-up effects, type of top-down effects and how consumer fitness effects are measured. We focused our analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
163
2
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 221 publications
(187 citation statements)
references
References 115 publications
7
163
2
4
Order By: Relevance
“…(Costello & Altieri, 1995;Wratten et al, 2007), our study shows that vegetation diversity can also contribute to decreasing the growth of the later wingless aphid populations. Finally, our laboratory results need to be confirmed at a larger scale under actual field crop conditions, where other parameters such as the interaction with natural enemies might play an important part in the final aphid control (Vidal & Murphy, 2018). Although additive vs. substitutive designs are often compared in studies of the effect of intercropping on pest control, little is reported about the influence of plant relative densities on pest dispersal (Lopes et al, 2016).…”
Section: Discussionmentioning
confidence: 88%
“…(Costello & Altieri, 1995;Wratten et al, 2007), our study shows that vegetation diversity can also contribute to decreasing the growth of the later wingless aphid populations. Finally, our laboratory results need to be confirmed at a larger scale under actual field crop conditions, where other parameters such as the interaction with natural enemies might play an important part in the final aphid control (Vidal & Murphy, 2018). Although additive vs. substitutive designs are often compared in studies of the effect of intercropping on pest control, little is reported about the influence of plant relative densities on pest dispersal (Lopes et al, 2016).…”
Section: Discussionmentioning
confidence: 88%
“…Similarly, our model of herbivore richness only explained 18.7% of the variation in herbivore richness, whereas our model of herbivore abundance was unsupported. When secondary consumer abundance was included as a predictor variable in our model of herbivore richness, model performance increased by approximately 10% (Figures and S10), which suggests an importance of top down pressures in our system (Vidal & Murphy, ). However, the addition of secondary consumer abundance to our model of herbivore abundance did not lead to a supported model (Figure S10).…”
Section: Discussionmentioning
confidence: 95%
“…While we have focused on bottom‐up mechanisms underlying insect communities on aspen, we recognize that top‐down factors (e.g., predation and parasitism) also influence insect herbivores (Katano, Doi, Eriksson, & Hillebrand, ; van Veen, Morris, & Godfray, ; Vidal & Murphy, ). A meta‐analysis by Vidal and Murphy () revealed that top‐down forces are often stronger than bottom‐up effects in influencing insect herbivore fitness. Yet, these differences varied across insect groups (e.g., specialist vs. generalist insects and across feeding guilds).…”
Section: Discussionmentioning
confidence: 99%